High-loading inducing Fe-dimer on carbon nitride promotes the generation of ·O2− - Xinran Zheng; Yuchao Wang; Jianping Guan; Xu Liu; Yu Bai; Yingbi Chen; Peiyao Yang; Jing Zhang; Houzheng Ou; Meng Wang; Yu Xiong; Haozhi Wang; et al. (Advanced Powder Materials, 2025)
The research on metal dimer clusters is of great importance, owing to the potential in modulating the adsorption behavior towards reaction intermediates. Here, we develop a loading heightening strategy to obtain a 32.5 ​wt% Fe-dimer catalyst (Fe-32.5). The co-anchoring of two Fe atoms in a single triazine ring of carbon nitride with an atomic spacing of ∼0.23 ​nm is proved. Fe atoms occupy the pores of the triazine ring in the lower iron content sample (Fe-12.9 and Fe-17.1). However, with the increase of iron content to 32.5 ​wt%, two Fe atoms simultaneously occupy one triazine ring. For Fe-32.5, besides the main peak located at ∼1.5 ​Å corresponding to the Fe–N interaction, a peak attributed to Fe–Fe bonding is observed at ∼2.2 ​Å in Fourier-transformed k3-weithted extended X-ray absorption fine structure. Density functional theoretical calculations reveal that Fe-dimer in Fe-32.5 induces a charge redistribution compared with that in Fe-12.9 and Fe-17.1. H2O∗ is adsorbed on O∗ via hydrogen bonding in Fe-12.9 and Fe-17.1. However, H2O∗and O∗ in Fe-32.5 are adsorbed on Fe–Fe dimer, resulting in a decrease in the total energy of the reaction process. For the two former, O2−∗ adsorbs on individual Fe atoms. Fe-dimer in Fe-32.5 adsorbs O2−∗ in the form of bridge bonds, which facilitates the ·O2− release. Furthermore, an enhanced affinity for the substrate 3,3′,5,5′-tetramethylbenzidine and higher peroxidase-like activity were displayed. This work provides an effective mean to synthesize metal dimer clusters through high loading.